2011
DOI: 10.1111/j.1399-6576.2011.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

No beneficial effects of levosimendan in acute porcine endotoxaemia

Abstract: Contrary to our hypothesis, levosimendan given in conjunction with a protocolized vasopressor and fluid resuscitation did not improve cardiac, renal or liver function in this model of acute porcine endotoxaemia. Hyperlactataemia, acidosis and increases in plasma pro-inflammatory cytokines were observed, the mechanisms and implications of which remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the present study, levosimendan did not attenuate the proinflammatory response to endotoxemia and MV in either plasma or the diaphragm (Figures 3 and 4 ). The lack of effect of levosimendan on plasma inflammation after levosimendan exposure is in line with previous studies [ 45 , 46 ]. In apparent contrast, in experimental sepsis induced by cecal ligation and incision, levosimendan did reduce high plasma levels of IL-1β [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, levosimendan did not attenuate the proinflammatory response to endotoxemia and MV in either plasma or the diaphragm (Figures 3 and 4 ). The lack of effect of levosimendan on plasma inflammation after levosimendan exposure is in line with previous studies [ 45 , 46 ]. In apparent contrast, in experimental sepsis induced by cecal ligation and incision, levosimendan did reduce high plasma levels of IL-1β [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, it was found that levosimendan increased coronary blood flow 19 . In contrast to these beneficial studies, negative results were described in a study with levosimendan in endotoxin‐induced PH in rats 22 . In this experiment, no improvement in RV or LV function was found and levosimendan was associated with hyperlactatemia, acidosis, and an increase in plasma proinflammatory cytokines.…”
Section: Levosimendan In Phmentioning
confidence: 79%
“…The effects of levosimendan on outcome are controversial, particularly in sepsis [128]. However, in certain situations, it may be advantageous; for example, levosimendan is a Ca 2+ sensitizer and inodilator, with immunomodulatory and antiapoptotic properties.…”
Section: Inotropic Agentsmentioning
confidence: 97%